2023
DOI: 10.1021/acs.jafc.3c01492
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Structurally Distinct Lycopene β-Cyclases for Production of the Cyclic C40 Carotenoids β-Carotene and Astaxanthin by Corynebacterium glutamicum

Abstract: Lycopene β-cyclase (EC 5.5.1.19) is one of the key enzymes in the biosynthesis of β-carotene and derived carotenoids. It catalyzes isomerase reactions to form β-carotene from lycopene by β-cyclization of both of its ψ-ends. Lycopene β-cyclases are widespread in nature. We systematically analyzed the phylogeny of lycopene β-cyclases from all kingdoms of life and predicted their transmembrane structures. To this end, a collection of previously characterized lycopene β-cyclase polypeptide sequences served as bait… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…In a recent study, alternative lycopene β-cyclases were identified that show a mitigated effect towards a possible feedback inhibition by various oxy-functionalized cyclic C40 carotenoids from astaxanthin biosynthesis, resulting in an improved total carotenoid biosynthesis in C. glutamicum 45 . Another study with H. pluvialis suggested that free astaxanthin could potentially inhibit its own biosynthesis and therefore the production of astaxanthin variants such as esterified astaxanthin was recommended 56 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, alternative lycopene β-cyclases were identified that show a mitigated effect towards a possible feedback inhibition by various oxy-functionalized cyclic C40 carotenoids from astaxanthin biosynthesis, resulting in an improved total carotenoid biosynthesis in C. glutamicum 45 . Another study with H. pluvialis suggested that free astaxanthin could potentially inhibit its own biosynthesis and therefore the production of astaxanthin variants such as esterified astaxanthin was recommended 56 .…”
Section: Discussionmentioning
confidence: 99%
“…It has been metabolically engineered for efficient production of various non-natural C40 carotenoids including astaxanthin 12 , 44 . Recently, a screening of structurally distinct lycopene β-cyclases revealed that higher astaxanthin production can be achieved with cytosolic lycopene β-cyclase from Synechococcus elongatus and membrane-bound heterodimeric lycopene β-cyclase from Brevibacterium linens 45 . However, upon expression of β-carotene hydroxylase or β-carotene ketolase genes, a reduction of total carotenoid occurs, which might be due to a yet to be defined feedback-inhibition of the carotenoid pathway upstream of β-carotene 45 .…”
Section: Introductionmentioning
confidence: 99%
“…The authors furthermore discovered a significant decrease in the total carotenoid content in the astaxanthin-producing strains and postulated a feedback inhibition of lycopene β-cyclases by astaxanthin or intermediates to be responsible for this effect. 6 The article "High-Yield Biosynthesis of trans-Nerolidol from Sugar and Glycerol" impressively demonstrates that the construction and optimization of highly efficient microbial cell factories still require a great deal of effort for testing high numbers of enzymes, strain modifications, and production parameters. The work aiming at Escherichia coli-based production of the sesquiterpene alcohol trans-nerolidol finally yielded a process that produced the pure trans form of nerolidol and could reach >90% of the theoretically possible product/substrate yield and a maximal yield of 16 g L −1 within 4 days.…”
Section: Conference Sessionsmentioning
confidence: 99%
“…A cytosolic cyclase from Synechococcus elongatus was found to be superior to the previously used enzyme from Pantoea ananatis , and a membrane-bound heterodimeric cyclase from Brevibacterium linens increased the concentrations of astaxanthin by 45%. The authors furthermore discovered a significant decrease in the total carotenoid content in the astaxanthin-producing strains and postulated a feedback inhibition of lycopene β-cyclases by astaxanthin or intermediates to be responsible for this effect …”
Section: Selected Contributions From the Specific Conference Sessionsmentioning
confidence: 99%
“…Astaxanthin (3,3′-dihydroxy-β,β-carotene-4,4′-dione) is a bioactive natural pigment with red-orange color that is part of the carotenoid family, widely used in the fields of nutraceuticals, cosmetics, and animal feed. Nowadays, quantities of astaxanthin can be industrially obtained by microorganisms. Structurally, astaxanthin contains multiple conjugated double bonds and chiral carbon atoms, and this unique structure endows it with geometric and optical isomers (Figure ). Optical isomers of astaxanthin widely exist in various biological sources; e.g., (3 S ,3′ S ) is the predominant stereoisomer in Haematococcus pluvialis (H.…”
Section: Introductionmentioning
confidence: 99%